Motivation Factors for Political Consciousness Formation in the Modern World - V. Balakhonsky, Vitaly; D. Shipunova, Olga; I. Strelchenko, Vasiliy; V. Balakhonskaya, Liudmila; V. Beresneva, Iuliia (International Journal of Criminology and Sociology, 2022)
The article deals with the problem of political consciousness formation in the global conditions of heterogeneous political structures, which generate a wide range of needs and interests of groups and individuals. The purpose of our study is to identify the motivational structure of the subject's consciousness formation in political structures of different types. Conceptual description of the motivational structure in socio-political systems requires complex application of various research methods. The authors utilize such methods as structural and functional analysis of the informational and social environment, the phenomenological analysis of the role of communicative practices in the public sphere driving the attitudes of mass consciousness in the process of political power legitimation. Empirical methods include public opinion polls. Following the typology of forms of political consciousness, it is possible to single out and to systematize objective system factors of the living environment and subject-oriented factors of consciousness manipulation in public policy. Remarkably, real social systems are characterized by the complex synthesis of elements from different types of political consciousness. The process of recognizing the legitimacy of power by an individual is defined by opposite motivational vectors of freedom and necessity and runs on the base of rational and emotional perception of the political situation. The unity of the diverse forms of political consciousness organization in the global society is based on the axiological consensus between cultures, between society and human, between state and person. These relations conceptually manifest in symbols that motivate individual and group consciousness to trust in power.